Evironmental sanitation and toddler diarrhea incidence: A cross-sectional study in Kanjilo, Indonesia - Awaliah, Nirwana Putri; Nildawati, Nildawati; Ansyar, Dian Ihwana; Syarfaini, Syarfaini (Sociality: Journal of Public Health Service, 2025)
Diarrhea remains a significant public health concern in Indonesia, particularly among toddlers, with high morbidity and mortality rates largely influenced by environmental sanitation. Despite extensive efforts, many regions continue to exhibit inadequate sanitation conditions. This study aimed to analyze the association between environmental sanitation factors and the incidence of diarrhea in children aged 12–59 months in the Kanjilo Health Center area, Gowa Regency. Employing a quantitative cross-sectional design, the study involved 331 purposively selected mothers of children under five from a population of 1,906. Data collection utilized structured questionnaires and was analyzed using the chi-square test. Findings revealed a significant relationship between diarrhea incidence and both the source of drinking water (p = 0.018) and waste bin condition (p = 0.033), while the wastewater disposal system was not significantly associated (p = 0.074). Among the participants, 39.9% reported toddlers with diarrhea episodes, indicating substantial exposure to environmental risk factors. These findings highlight the need for targeted interventions to enhance water safety and solid waste management in rural health settings. Strengthening sanitation infrastructure may substantially reduce diarrhea incidence among toddlers, thereby improving child health outcomes in rural Indonesian communities.